Adoption of blockchain in supply chain: an analysis of influencing factors. Issue 3 (22nd April 2020) - Ghode, Dnyaneshwar; Yadav, Vinod; Jain, Rakesh; Soni, Gunjan
Abstract : Purpose: Blockchain technology (BT) is setting world-shattering standard in all type of transactions in business. BT has the prospective to drastically transform supply chain (SC). The main challenge is to enhance trust among the SC stakeholders. This paper aims to identify and prioritize the factors and its challenges that influence the adoptability of BT in SC. The prioritization of these factors will be helpful to the practitioners to decide the strategy of implementing the BT in SC. Design/methodology/approach: The factors influencing adoption of BT are identified from the review of literature and expert opinion is used to rank the factors influencing the adoptability of BT in SC using grey relational analysis (GRA). Findings: We identified and prioritized key factors: inter-organizational trust and relational governance as organizational challenge, data transparency and data immutability as technological challenge, interoperability and product type as operational challenge and social influence and behavioral intention as social challenge that influences adoptability of BT in SC. Originality/value: The priority of these factors will guide future researchers and industry practitioners to plan rational and financial strategy for implementing BT in SC.